Ensuring IP services consistency through lightweight monitoring-based admission control - Lima, Solange (2006)
This paper evaluates the performance of a distributed and lightweight AC model based on per-class edge-to-edge monitoring feedback for ensuring the quality of multiple services in class-based IP networks. The model resorts to service-dependent AC rules for controlling QoS parameters and SLSs utilization, both intradomain and end-to-end. To provide a proof-of-concept of the proposed AC solution, a prototype of the AC model has been developed and tested using a simulation platform. The devised test scenarios aim at exploring the AC criteria's ability in satisfying each service class QoS levels and existing SLSs commitments. Generically, the results show that the proposed AC model, using a two-rule AC criterion defined on a service class basis, is able to control service levels and achieve high network utilization, without adding significant complexity to the network elements. The use of systematic edge-to-edge on-line monitoring and of a controlled degree of overprovisioning proved to be essential design aspects contributing for reaching a good compromise between simplicity and performance.